The Effect of Human Resources on Capital of Worker Cooperative - Suyanto, Suyanto (UI Scholars Hub, 2012)
There are several business problems which hampers sustainability of worker cooperatives in Indonesia. They have inadequate capital to support businesses run by cooperatives and the government provides insufficient support for the worker cooperatives. The problem under study is how human resources management affected the capital of worker cooperatives. The study used explanatory approach by employing a census to collect data from 11 existing worker cooperatives in the loading and unloading services in port cities across Java. The data collected was then analyzed with the Path Analysis. Research findings indicate that human resources practices of members, administrators, and managers were significant in affecting the capital of cooperatives simultaneously. However, when analyzed partially, influence of each variable was mixed. Partially, the human resource practices of members does not have a significant effect, while the administrators do have positive effect and the managers have negative effect. The administrator is considered the most important determinant of capital in cooperatives. Thus, it is recommended that worker cooperatives should pay attention to provide member educational and professional trainings and improve administrator quality in raising and making use of capital more efficiently. For further research, it is suggested to study the impact of human capital on other types of cooperatives.